Economics : its concepts and principles (with agrarian reform and taxation) - Gabay, Bon Kristoffer G; Remotin, Roberto M. Jr; Uy, Edgar Allan M. (Manila, 2007)
The elements of this textbook are not limited in their application to a particular country, bit its illustration of economic principles requires educational and institutional settings.
Keywords: economics